2016
DOI: 10.1186/s12950-016-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate is a novel anti-inflammatory agent to treat multiple inflammatory organ injuries

Abstract: Ethyl pyruvate (EP) is a simple derivative of pyruvic acid, which is an important endogenous metabolite that can scavenge reactive oxygen species (ROS). Treatment with EP is able to ameliorate systemic inflammation and multiple organ dysfunctions in multiple animal models, such as acute pancreatitis, alcoholic liver injury, acute respiratory distress syndrome (ARDS), acute viral myocarditis, acute kidney injury and sepsis. Recent studies have demonstrated that prolonged treatment with EP can ameliorate experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 93 publications
(174 reference statements)
0
44
0
Order By: Relevance
“…To test this hypothesis, we investigated whether inhibition of HMGB1 secretion by the simple aliphatic ester of pyruvic acid, ethyl pyruvate (EP), decreases diabetes-related hepatocellular damage, suppresses activation of inflammatory cascades from TLR4, and modulates the inflammatory status. By virtue of its ability to ameliorate multiple acute inflammatory organ injuries in experimental animal models, EP acts as an anti-inflammatory agent [45]. More importantly, a part of its anti-inflammatory properties include it capability to downregulate HMGB1 release [37].…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we investigated whether inhibition of HMGB1 secretion by the simple aliphatic ester of pyruvic acid, ethyl pyruvate (EP), decreases diabetes-related hepatocellular damage, suppresses activation of inflammatory cascades from TLR4, and modulates the inflammatory status. By virtue of its ability to ameliorate multiple acute inflammatory organ injuries in experimental animal models, EP acts as an anti-inflammatory agent [45]. More importantly, a part of its anti-inflammatory properties include it capability to downregulate HMGB1 release [37].…”
Section: Introductionmentioning
confidence: 99%
“…Our results imply that the concept of a strict dichotomy between glycolysis and oxidative phosphorylation as energy sources for effector T cells and Treg, respectively, may be over-simplistic and, therefore, targeting the glycolytic pathway for Treg expansion and suppressive function by EP could be beneficial. Thus far, EP has been shown to be safe when tested in both healthy human volunteers and heart surgery patients [ 2 , 38 ]. Our data suggest that the utilization of EP may be a promising supporting therapy for autoimmune and immunoinflammatory diseases in which the enhancement of Treg numbers and suppressive functions is expected to dampen disease activity and progression.…”
Section: Discussionmentioning
confidence: 99%
“…While pyruvate is very effective for in vitro experiments in protecting acinar cells against L-Asparaginase-triggered damage [39], a simple derivative of pyruvic acid, namely, ethyl pyruvate has been found useful for treatment of bile-induced AP in a rat model [54]. Ethyl pyruvate is also known as a ROS scavenger and, in addition, has other anti-inflammatory effects [55]. The role of ROS in AP remains controversial [30,56,57,58], while a recent study has shown an important contribution of nitric oxide [31] in pancreatic pathology, justifying the use of NO synthase inhibitors as a potential AP treatment [59,60].…”
Section: How To Save Pacs From Ca 2+ Overload and Necrosis?mentioning
confidence: 99%